Georges de La Tour and the enigma of the visible - Judovitz, Dalia (Fordham University Press, 2018)
This interdisciplinary study explores George de La Tour's (1593-1652) enigmatic representations of light, vision and the visible in order to question the nature of painting and its religious, artistic and conceptual aspects. Challenging the familiarity of vision, it proposes a spiritual understanding of painting and its engagements with the world.